2022
DOI: 10.48550/arxiv.2202.09647
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experimental demonstration of composite pulses on IBM's quantum computer

Abstract: We perform comprehensive experimental tests of various composite pulse sequences using one of open-access IBM's quantum processors, based on superconducting transmon qubits. We implement explicit pulse control of the qubit by making use of the opportunity of low-level access to the backend, provided by IBM Quantum. We obtain the excitation profiles for a huge variety of broadband, narrowband, and passband composite pulses, producing any pre-chosen target probabilities, ranging from zero to one. We also test un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Another scheme for robust frequency conversion that was suggested recently is the composite segmented (CS) scheme, which was adopted from NMR. In the past half a century, rich research activities in NMR allowed the use of composite pulses schemes for robust control and preparation of a desired superposition state in atomic two-level systems [19,20], and for coherent quantum control [21][22][23][24][25][26]. In the NLO realm, Rangelov et al [27] and Erlich et al [28] showed numerically and experimentally that a novel method using a CS crystal design based on the NMR composite pulses scheme of Shaka and Pines [29] can be used in NLO to create a broadband and robust second harmonic generation (SHG) process.…”
Section: Introductionmentioning
confidence: 99%
“…Another scheme for robust frequency conversion that was suggested recently is the composite segmented (CS) scheme, which was adopted from NMR. In the past half a century, rich research activities in NMR allowed the use of composite pulses schemes for robust control and preparation of a desired superposition state in atomic two-level systems [19,20], and for coherent quantum control [21][22][23][24][25][26]. In the NLO realm, Rangelov et al [27] and Erlich et al [28] showed numerically and experimentally that a novel method using a CS crystal design based on the NMR composite pulses scheme of Shaka and Pines [29] can be used in NLO to create a broadband and robust second harmonic generation (SHG) process.…”
Section: Introductionmentioning
confidence: 99%
“…Various signal distortions from rf field inhomogeneities, offresonance effects and field amplitude error were reduced to a very low order of correction by means of complex sequences of pulses adapted to single or even dual compensation of these systematics. Composite pulses have also demonstrated to be useful for robust error compensation in high-fidelity qubit gates dedicated to quantum computation [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…First developed in nuclear magnetic resonance (NMR) [1] and its analogue even earlier in polarization optics [2], their efficiency was soon largely acknowledged. In the last two decades, they have been successfully applied in other areas, such as trapped ions [3][4][5][6][7][8][9][10], neutral atoms [11,12], quantum dots [13][14][15][16][17][18], NV centers in diamond [19], doped solids [20][21][22][23], superconducting qubits [24,25], optical clocks [26], atom optics [27][28][29], magnetometry [30], optomechanics [31], etc.…”
mentioning
confidence: 99%
“…Traditionally, composite pulses are primarily used to achieve broadband excitation profiles [25,[32][33][34] with high fidelity, robust to deviations in certain experimental parameters, such as the amplitude, frequency and duration of the external driving pulsed fields. Recently, composite pulses which are robust to deviations in any parameter have been designed and demonstrated [21].…”
mentioning
confidence: 99%
See 1 more Smart Citation